EVALUATION OF IMPLEMENTATION OF VIRTUAL SYNCHRONOUS LEARNING MODA IN TEACHER TRAINING - Kamilia Fitria Fii Silmi K; Laksmi Dewi (Indonesian Journal of Multidisciplinary Science, 2022)
Virtually based training is an alternative way for academics and training to equip students with the skills necessary for any career. The synchronous learning mode as a training mode is considered effective in improving the skills of digital educators, especially in the digital era of the 21st century. The use of this mode is increasing, but its effect on learning retention in teacher training has not scientifically proven. This study aims to implement a HOTS-based training program using synchronous learning media at an educational technology-based company. The research method used is descriptive-quantitative to obtain an overview of the implementation of the training from the aspects of reactions, cognitive understanding, and learning outcomes that are applied after. The results showed that the participants' reaction to the training followed by using synchronous learning mode were very good, there was a change in understanding related to HOTS learning between before training and before training it could be applied in the day-to-day teaching process.